Defective Transcriptional Programming of Effector CD8 T Cells in Aged Mice Is Cell-Extrinsic and Can Be Corrected by Administration of IL-12 and IL-18 - Jergović, Mladen; Thompson, Heather L.; Renkema, Kristin R.; Smithey, Megan J.; Nikolich-Žugich, Janko (Frontiers in Immunology, 2019)
In response to infection with intracellular microorganisms, old mice mobilize decreased numbers of antigen-specific CD8 T cells with reduced expression of effector molecules and impaired cytolytic activity. Molecular mechanisms behind these defects and the cell-intrinsic (affecting naïve CD8 T cells themselves) vs. extrinsic, microenvironmental origin of such defects remain unclear. Using reciprocal transfer experiments of highly purified naïve T cells from adult and old transgenic OT-1 mice we decisively show that the dominant effect is cell-extrinsic. Naïve adult OT-1 T cells failed to expand and terminally differentiate in the old organism infected with Listeria-OVA. This defect was preceded by blunted expression of the master transcription factor T-bet and impaired glycolytic switch when T cells are primed in the old organism. However, both old and adult naïve CD8 T cells proliferated and produced effector molecules to a similar extent when stimulated in vitro with polyclonal stimuli, as well as when transferred into adult recipients. Multiple inflammatory cytokines with direct effects on T cell effector differentiation were decreased in spleens of old animals, particularly IL-12 and IL-18. Of note, in vivo treatment of mice with IL-12 and IL-18 on days 4-6 of Listeria infection reconstituted cytotoxic T cell response of aged mice to the level of adult. Therefore, critical cytokine signals which are underproduced in the old priming environment can restore proper transcriptional programming of old naïve CD8 T cells and improve immune defense against intracellular microorganisms.